An investigation into students‟ low performance in English language at „O‟ level in Gweru Urban High Schools. - Mucheke, Noreen (Midlands State University, 2020)
This study is an investigation into the causes of the low performance in the English Language at „O‟ Level in high schools in Gweru Urban. It is guided by the following objectives, to find out factors that contribute to the low pass rate in the English Language at Ordinary level in Gweru Urban Schools. The study seeks to also interrogate the possible remedies that schools could harness to arrest the low performance. To carry out the research, the survey method was used in the selected schools in Gweru Urban and the respondents included headmasters, selected teachers and students in the target population. To make use the research instruments would work, the researcher used them in a pilot project that enabled her to fine tune her instruments before implementing them on the selected case study. The study found out that the major causes for the low performance in the English Language include but are not limited to the following: lack of teaching and learning materials in schools, little exposure to the English Language in the home, teachers giving discouraging comments in their marking of students‟ work, poverty among students, the teachers‟ limited teaching strategies and the poor working conditions that characterise Zimbabwean teachers since the crisis decade, (1998- 2008). The study also highlighted the possible measures that could help in uplifting the low performance in the English Language. These included the provision of better learning and teaching materials in schools, greater parents‟ involvement in the education of their children, varied teaching strategies and improving the working conditions of teachers. From the findings, the study made a number of recommendations to parents, schools and the Ministry of Primary and Secondary Education among them being that the Government should continue to fund the education sector so that poor children are not disadvantaged.